Responsabilidade Social e a Demonstração do Valor Adicionado - César Eduardo Stevens Kroetz (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2008)
The companies are considered fundamental and strategical components for the economical, environmental and social development. Therefore, the contemporary society has demanded answers from these organizations regarding to their commitment with the economical development and with the social and environmental responsibilities. That provoked in the business class the necessity to propose demonstrations to present the organizational contribution regarding its generation and wealth distribution. This study has the objective to ponder and introduce a discussion about this issue, approaching aspects related with the social responsibility, the theory of the stake holders, the economical and accounting added value and the demonstration of the added value.